(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This text explores Ibn Sina’s classification of sciences and his understanding of human practical activity, which he explains as developing along three main directions. It highlights Ibn Sina’s method of evaluating sciences based on their connection to human behavior, existence, and their practical significance in daily life. The discussion further emphasizes the respect given to prominent Muslim scholars of the 10th and 11th centuries—such as Muhammad Khwarizmi, al-Farabi, Ibn Sina, and al-Biruni—whose contributions significantly influenced both Eastern and Western intellectual traditions. The annotation also covers al-Biruni’s scientific legacy in social sciences, affirming his status as a great medieval naturalist and philosopher who made lasting contributions to philosophy, history, and philology. The enduring philosophical views of these scholars on the coexistence of religion and philosophy are noted, particularly their rational approach to faith and divine existence.